Stability of Trash Trap Design in Various River Estuary - Hairullah Hairullah; Tri Harianto; Achmad Bakri Muhiddin; Upe Zahra (International Association of Lowland Technology, 2023)
In Indonesia, the most serious issue is garbage. As a result, with a total waste of 1.92 million tons, it has been named the number two contributor of plastic waste to the sea. Garbage disposal in the river can be harmful to downstream residents, especially fishermen. Because of the accumulation of garbage in the riverbed, the river becomes very shallow, causing the water to overflow when it rains, which can cause flooding. The goal of this final project is to design superstructure and substructure dimensions and reinforcement. To reduce waste entering the sea, trash traps are built in estuaries by filtering surface waste. The Floating Trash Trap model, as well as its dimensions and sizes, is the scheme and design of the planned trash trap. The focus of the superstructure is on the control of steel profiles and bolt anchors, while the focus of the substructure is on the foundation. SAP 2000 software was used for structural design analysis. The superstructure design results were safe for all existing loading combinations.